The Work of the Joint Dissertation Board of the RFCFS and the RUDN University - E. V. Chesnokova (Теория и практика судебной экспертизы, 2017)
The paper reports on the work of the dissertation board jointly run by two organizations – the Russian Federal Center of Forensic Science of the Russian Ministry of Justice and Peoples’ Friendship University of Russia. Included is an overview of dissertations defended in the year 2016 and early 2017. Conclusions are drawn regarding the role of the dissertation board in advancing forensic science and improving the quality of scientific manpower development.